K-factor due to implementing of DC unbalanced/balanced of a transformer - Syafruddin, Hasan; Ismail, Daut, Prof. Dr.; Soib, Taib, Assoc. Prof. Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/